2000
DOI: 10.1007/pl00014048
|View full text |Cite
|
Sign up to set email alerts
|

SEREX analysis of gastric cancer antigens

Abstract: Stomach cancer is the major malignancy in Japan and one of the most common cancers worldwide. To establish the basis for an immunotherapeutic approach to stomach cancer, we have initiated an analysis of stomach cancer antigens recognized by human immunoglobulin G (IgG) antibodies using SE-REX, a powerful expression cloning method developed by Dr. M. Pfreundschuh's group. Five stomach cancer cDNA libraries have been screened with autologous patient sera: one moderately differentiated adenocarcinoma; two poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Greiner et al [22] also demonstrated significant antibody response toward MPP11 in the sera of breast cancer patients but not in sera of healthy volunteers. These data contradict the data of Obata et al [21] and Scanlan et al [20] who both failed to show increased immunogenicity of ZRF1 antigen in sera of stomach and breast cancer patients correspondingly compared with sera of healthy women. This concordance was explained by Greiner in part by different cDNAs lengths of SEREX clones that might result in a various conformation of the gene's protein products and subsequently in a different epitope presentation to IgG antibodies [22].…”
Section: Discussioncontrasting
confidence: 99%
“…Greiner et al [22] also demonstrated significant antibody response toward MPP11 in the sera of breast cancer patients but not in sera of healthy volunteers. These data contradict the data of Obata et al [21] and Scanlan et al [20] who both failed to show increased immunogenicity of ZRF1 antigen in sera of stomach and breast cancer patients correspondingly compared with sera of healthy women. This concordance was explained by Greiner in part by different cDNAs lengths of SEREX clones that might result in a various conformation of the gene's protein products and subsequently in a different epitope presentation to IgG antibodies [22].…”
Section: Discussioncontrasting
confidence: 99%
“…This technology aimed to identify the complete repertoire of immunogenic gene products in human cancer, also known as the "cancer immunome". Several SEREX studies have focused on identifying tumor antigens in melanoma [41,42], esophageal cancer [43], colon cancer [44][45][46], gastric cancer [47][48], renal cancer [49,50] and breast cancer [51,52].…”
Section: Identification Of B Cell Epitopesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The most rapidly expanding group of tumor Ags are the cancer/testis (C/T) Ags, which are either not expressed or are present at very low levels in normal tissues except the testes and perhaps the placenta. 12,13 Because the testes are not patrolled by the immune system, expression of C/T Ags in this environment is not harmful.…”
Section: Introductionmentioning
confidence: 99%